GROWTH RESPONSE OF ADVENTIVE SHOOT GINGER PLANTS TO THE ADMINISTRATION OF ZPT FROM SHALLOT EXTRACT - Nurlaela; Eka Sudartik; Ahmad Zailan (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
This study aims to activate the growth response of ginger (Zingiber officinale var. amarum) shoots to the application of plant growth regulators (PGRs) from shallot extract (Allium cepa) with concentrations of 0 ml (control), 15 ml, 25 ml, and 30 ml using a completely randomized design (CRD) with six replications. The parameters observed included the length of adventitious shoots (5, 15, 30 days after planting), the time of shoot emergence (days after planting), and the speed of shoot growth (cm/day), analyzed by ANOVA and the BNJ test at a 5% level. The results showed that application of shallot extract had a very significant effect on shoot length at 5 days after planting (F-count 7.04 > F-table 4.94) with the 30 ml treatment (P3) reaching 0.90 cm, significantly different from the control (0.22 cm). The time of shoot emergence was also very significant (F-count 9.23 > F-table 4.94), the fastest in P3 (2.33 days) compared to the control (5.00 days). However, the speed of shoot growth was not significant (F-count 1.81 < F-table 3.10), although P3 was the highest (0.198 cm/day). Shallot extract is effective as a natural PGR to stimulate early shoot initiation. Keywords: Adventitious shoots, Red onion extract, ZPT